State and capital in the context of COVID-19 in India: Some implications for globalisation - Praveen K. Jha; Meghna Goyal (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2023)
The interdependence of the State and business is widely recognised across many disciplines and frameworks. This paper examines the State-capital nexus in India during the neoliberal era, focusing on how the State has facilitated accelerated primitive accumulation for large capital by selectively promoting certain economic policies while neglecting others, compromising public expenditures, and implementing social policy only sparingly. These tendencies have given rise to growing inequality of income, wealth, and opportunities, as well as an increasing trend of dispossession. Notably, the COVID-19 pandemic served as a catalyst for the Indian government to expedite these processes at an alarming rate. Consequently, crony relationships are becoming increasingly evident in India, wherein a select group of favoured conglomerates reap exclusive benefits.
Keywords: P16; H10; 330; crony capitalism; COVID-19; business-state relationship; public policy; corporate profit